Ploidy variation in the cultivated yams (Dioscorea cayenensisDioscorea rotundata complex) from Cameroon as determined by flow cytometry - Dansi, A.; Mignouna, H.; Pillay, M.; Zok, S. (2001)
The ploidy levels of the twenty-two yam (Dioscorea cayenensis-D. rotundata complex) cultivars within germplasm Cameroon Guinea yam were determined by flow cytometry. Three different ploidy levels (4x,6x, 8x) were detected within the samples analysed. Fifteen cultivars were tetraploids, five were hexaploids, and two were octoploids. The cultivar group EKOTO showed a high level of ploidy variation with tetraploid, hexaploid and octoploid cultivars. The hexaploid nature of cultivars Dobnawo and Bilougnou supported the hypothesis that they are hybrids between cultivars of the EKOTO group and either the KPE or BAKOKAE groups.